Sustainable Tourism Development In Petak Gianyar Village, Bali: Potentials And Challenges - Wisnawa, I Made Bayu; Widari, Dewa Ayu Diyah Sri (Language Assistance, 2025)
Petak Village, located in Gianyar, Bali, possesses great potential for agriculture-based tourism due to its rich nature and culture. The available tourism amenities include waterfalls, trekking paths, spiritual tourism, and other activities based on local wisdom. However, tourism in the village is still challenged by inadequate infrastructure, insufficient marketing, a lack of community participation in the management, and several other factors. This is the main reason this research is conducted, to uncover the tourism potential and challenges of Petak Village in the context of sustainable tourism. The employed strategy centres on qualitative methods with a descriptive approach which features observations, document analysis, and Focus Group Discussions (FGDs) with key stakeholders from the local community, village administration, and tourism entrepreneurs. Based on the focus group discussions, we found that Petak Village has significant opportunities to be further developed into a natural and cultural centre, which would enhance the enduring economic livelihoods of the residents. However, they lack sufficient regulations for effective tourism management, coordination among the myriad stakeholders, a workforce, stronger communities and other regional developmental bodies, the active collaboration of public sectors, and nurture for infrastructure. This study's conclusion verifies that the Petak Village sustainable tourism development shall consider the preservation of the environment, the well-being of the local community, and the area's economic activities in a unified manner involving all relevant participants.